Infection of rotavirus in dairy calves in south Vietnam - Kyle, Helena (2007)
Rotavirus A is a double stranded RNA commonly considered to cause diarrhoea in young calves. There is no specific treatment for the disease and it can become economically devastating to the farmer. In this investigation 120 faecal samples were collected from dairy calves in South Vietnam in order to estimate the occurrence and importance of rotavirus infection in the country. The samples were also used for a co-operating study of the protozoan parasite Cryptosporidium parvum. The calves were younger than two months old and both diarrhoeic and non diarrhoeic individuals were sampled. Half the samples were collected at state farms with herd sizes of several hundred cows and the other half were from household farms with 1 and 100 cows. The samples were analysed for presence of rotavirus A by ELISA.